Music Education for Every Child - Idea or Reality? - Blaženka Bačlija Susić (University of Maribor Press, 2017)
Contemporary pedagogical, psychological and sociological research highlight the need for music education available to every child. Starting from the fundamental point of view according to which music affects the development of the child's whole personality, this idea stands out in history since the 17th century. Various educators in the late nineteenth and early twentieth century emphasized the importance of music education for every child. With historical and theoretical overview of this idea, this paper tries to examine the possibility of its realization in contemporary educational practice. The Venezuelan music education program El Sistema, that promotes humanistic idea of changing society through classical music education stands out as a unique example of a good practice. As a form of music education which particularly promotes the idea of availability of music to every child, the conception of Functional Music Pedagogy by the Croatian music pedagogue Elly Bašić (1908-1998) was shown as well. Considering the status of music in American educational policy, it is indicated as a significant change, in which the music is recognized as an educational priority for the first time in the history of education and it became the basic academic subject in the American federal education policy plan, as well as unprecedentedly incorporated in the federal law.